Synthesis of YAG Nano-powders and Transparent Ceramic by Microwave Homogeneous Precipitation - Jiang, Fenghua; Zhao, Degan; Wang, Jieqiang (Asian Journal of Chemistry, 2013)
In this study, yttrium oxide, nitric acid, aluminum nitrate, urea and ammonium sulfate were used as raw materials to synthesize YAG nano powder by microwave homogeneous precipitation. The synthesized YAG nano-powders were analyzed and characterized by TG, XRD and SEM. Effects of initial concentration and calcination temperature on the average size of powder were studied. The results showed that the average diameter of YAG nano-powder is 84 nm under the optimized conditions. The green body of transparent ceramic, which is 13 mm in diameter and 3 mm in thickness, was calcined and prepared at 1500 ºC for 4 h under the unidirectional pressing. The microstructure of the green body was also studied.